Anode black powder and recovery method thereof
The positive electrode sheet of the lithium battery is processed through laser cleaning technology, which solves the problem of low separation efficiency between the positive electrode black powder and aluminum foil in lithium battery recycling, and achieves the effect of efficient lithium recycling and reduces the recycling cost.
Patent Information
- Application Number
- CN202411975511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
During the lithium battery recycling process, it is difficult for the prior art to efficiently separate the positive electrode black powder and aluminum foil, resulting in low recycling efficiency and high cost.
The positive electrode sheet of the retired lithium battery was cleaned by laser cleaning technology, and the ratio of the characteristic diffraction peak of 311 and the characteristic diffraction peak of 200 in the X-ray diffraction pattern was controlled to be between 2 and 3.7, and a positive electrode black powder with excellent particle size distribution and low impurity content was obtained.
The efficiency of leaching lithium is improved by wet recycling, the subsequent recycling process is simplified, the recycling cost is reduced, and the recovery rate and dispersion of the positive electrode black powder are significantly improved.
Smart Images

Figure CN119786785A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary battery recycling, and in particular to a positive electrode black powder and a recycling method thereof. Background Art
[0002] With the large-scale application of lithium batteries in new energy vehicles and energy storage, the number of retired and scrapped lithium batteries has increased rapidly. The harmless treatment and resource utilization of lithium batteries can effectively avoid environmental pollution and resource waste, and at the same time have great economic benefits. In the process of dismantling and recycling retired lithium batteries, achieving efficient separation of positive electrode black powder and aluminum foil and obtaining positive electrode black powder with high dispersion and low impurity content is the key link to improve the recovery rate of iron-lithium materials. Summary of the invention
[0003] The purpose of the present application is to provide a positive electrode black powder and a recovery method thereof, so as to improve the efficiency of wet recovery of leached lithium, simplify the subsequent recovery process, and reduce the recovery cost.
[0004] To achieve the above-mentioned object, in a first aspect of the present application, a positive electrode black powder is provided, wherein the positive electrode black powder comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I (200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200) It is the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder.
[0005] As an implementation scheme of the present application, the positive electrode black powder satisfies: 0.22°≤F(311)≤0.31°, wherein F(311) is the half-peak width of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder.
[0006] As an embodiment of the present application, the positive electrode black powder satisfies: 0.15°≤F (200) ≤0.4°, where F (200) It is the half-peak width of the 200 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder.
[0007] As an implementation scheme of the present application, the height H2 of the characteristic peak with the largest particle size and the height H1 of the characteristic peak with the highest volume percentage in the particle size distribution diagram of the positive electrode black powder satisfy: 0.12≤H2 / (H1+H2)≤0.23.
[0008] As an embodiment of the present application, the positive electrode black powder contains impurity elements, the impurity elements contain Al element, the content of the Al element is A, and satisfies: A≤2.5wt%.
[0009] As an implementation scheme of the present application, the positive electrode black powder contains impurity elements, and the impurity elements include at least one of Al, Cu, Mg, B, Ca, W, Cr, Zr, Ti, La, and V. The total content of the impurity elements is C, satisfying: C≤3wt%.
[0010] As an embodiment of the present application, the specific surface area B of the positive electrode black powder satisfies: 3.3m 2 / g≤B≤7m 2 / g.
[0011] As an implementation scheme of the present application, the powder conductivity K of the positive electrode black powder 20KN satisfies: 0.05S / cm≤K≤0.35S / cm.
[0012] As an embodiment of the present application, the tap density TD of the positive electrode black powder satisfies: TD≤1.12g / cm 3 .
[0013] The second aspect of the present application provides a method for recovering positive electrode black powder, comprising the following steps:
[0014] S1. Discharging the retired lithium-ion battery and disassembling it to obtain the positive electrode sheet;
[0015] S2. Place the positive electrode sheet into a laser cleaning machine, and clean each surface of the positive electrode sheet for 0.75h to 4h at a laser wavelength of 405nm to 976nm and a cleaning power of 100W to 1000W, and then sieve to obtain positive electrode black powder;
[0016] The positive electrode black powder comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I (200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200) It is the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder.
[0017] Compared with the prior art, the beneficial effects of this application are:
[0018] The positive electrode black powder of the present application comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I (200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200)The peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder is controlled within a certain range by controlling the peak intensity ratio of the 311 characteristic diffraction peak to the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder, thereby improving the efficiency of wet recovery of leached lithium, simplifying the subsequent recovery process and reducing the recovery cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the X-ray diffraction pattern of the positive electrode black powder prepared in Example 1;
[0020] Figure 2 This is the particle size distribution diagram of the positive electrode black powder prepared in Example 1. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0022] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0023] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0024] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0025] Positive electrode black powder is mainly a mixture of decomposition products of positive electrode active material, conductive agent and binder. The impurity elements mainly come from doping coating elements in the positive electrode active material, side reaction products at the positive electrode / electrolyte interface and damaged aluminum foil.
[0026] An embodiment of the present application provides a positive electrode black powder, wherein the positive electrode black powder is obtained by laser cleaning a positive electrode plate. The positive electrode black powder of the present application comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I(200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200) It is the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder.
[0027] The inventors of this application have found that the ratio of the peak intensity of the 311 characteristic diffraction peak and the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder can reflect the content of aluminum impurities to a certain extent. By controlling the ratio of the two within the scope of this application, the leaching efficiency can be improved, which is conducive to simplifying the subsequent recovery process and reducing the recovery cost. The method for obtaining the X-ray diffraction spectrum of the positive electrode black powder in this application is as follows: grind the sample to be tested into powder for 15 minutes, and press it into a uniform thin sheet, then load the sample onto the sample stage of the X-ray diffractometer, and start the X-ray diffractometer to obtain the corresponding X-ray diffraction spectrum. The parameters of the X-ray diffractometer are as follows: target material: Cu target; X-ray measurement wavelength: 1.5406; scanning mode: continuous scanning; starting angle & ending angle: 10°~90°; scanning speed: 10° / min; step size: 0.01°.
[0028] In some embodiments, the positive electrode black powder satisfies: 2≤I (311) / I (200) ≤3.7.
[0029] In some embodiments, the positive electrode black powder satisfies: 0.22°≤F (311) ≤0.31°, where F (311) is the half-peak width of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder. Exemplarily, the half-peak width of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder can be 0.22°, 0.24°, 0.26°, 0.28°, 0.31°, or a value in the range formed by any two of the above points.
[0030] In some embodiments, the positive electrode black powder satisfies: 0.15°≤F (200) ≤0.4°, where F (200) is the half-peak width of the 200 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder. Exemplarily, the half-peak width of the 200 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder can be 0.15°, 0.2°, 0.25°, 0.3°, 0.35°, 0.4° or a value in the range formed by any two of the above points.
[0031] In this application (311) and F (200) Within the above range, it is beneficial to improve the leaching efficiency.
[0032] In some embodiments, there are at least two characteristic peaks in the particle size distribution diagram of the positive electrode black powder, and there is at least one characteristic peak above 20 μm, and the height H2 of the characteristic peak with the largest particle size and the height H1 of the characteristic peak with the highest volume percentage in the particle size distribution diagram of the positive electrode black powder satisfy: 0.12≤H2 / (H1+H2)≤0.23. Exemplarily, H2 / (H1+H2) can be 0.12, 0.15, 0.18, 0.2, 0.23 or a value in the range formed by any two of the above points. When H2 and H1 satisfy the above relationship, the content of large-particle aluminum foil mixed in the laser cleaning process accounts for a small proportion of the positive electrode black powder, and can be separated through the subsequent screening process, which effectively controls the Al impurity content and is conducive to simplifying the subsequent recycling process and reducing the recycling cost.
[0033] In some embodiments, the positive electrode black powder contains impurity elements, the impurity elements contain Al elements, the content of the Al element is A, and satisfies: A≤2.5wt%. Exemplarily, the content A of the Al element in the positive electrode black powder can be 0.1wt%, 0.5wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.5wt% or a value in the range formed by any two of the above points. In some embodiments, the content of the Al element is A, and satisfies: 0.5wt%≤A≤2.5wt%. The content of the Al element in the positive electrode black powder is within the above range, indicating that the recycling process effectively strips the positive electrode coating and the aluminum foil, significantly reducing the Al impurity content of the positive electrode black powder, which is conducive to simplifying the subsequent recycling process and reducing the recycling cost.
[0034] In some embodiments, the positive electrode black powder contains impurity elements, and the impurity elements contain at least one of Al, Cu, Mg, B, Ca, W, Cr, Zr, Ti, La, and V.
[0035] In some embodiments, the total content of the impurity elements is C, satisfying: C ≤ 3wt%. Exemplarily, the total content C of the impurity elements can be 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% or a value in the range formed by any two of the above points. In some embodiments, the total content of the impurity elements is C, satisfying: 0.7wt% ≤ C ≤ 3wt%. The total content C of the impurity elements is within the above range, which effectively reduces the process costs such as chemical impurity removal and sewage treatment in the subsequent recovery process of the positive electrode black powder, and reduces the recovery cost.
[0036] In some embodiments, the specific surface area B of the positive electrode black powder satisfies: 3.3 m 2 / g≤B≤7m 2 / g. Exemplarily, the specific surface area B of the positive electrode black powder can be 3.3m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g or a value in the range formed by any two of the above points. The specific surface area of the positive electrode black powder is within the above range, which is beneficial to the leaching and recovery of Fe and Li elements in the subsequent wet recovery process.
[0037] In some embodiments, the powder conductivity K of the positive black powder 20KN satisfies: 0.05S / cm≤K≤0.35S / cm. Exemplarily, the powder conductivity K of the positive black powder 20KN can be 0.05S / cm, 0.08S / cm, 0.1S / cm, 0.15S / cm, 0.2S / cm, 0.25S / cm, 0.3S / cm, 0.35S / cm, or a value in the range formed by any two of the above points. The powder conductivity of the positive black powder is within the above range, which is conducive to improving the subsequent recovery rate of Fe and Li elements.
[0038] In some embodiments, the tap density TD of the positive electrode black powder satisfies: TD≤1.12 g / cm 3 For example, the tap density TD of the positive electrode black powder may be 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.12g / cm 3 Or a value in the range formed by any two of the above points. In some embodiments, the tap density TD of the positive electrode black powder satisfies: 0.9≤TD≤1.12 g / cm 3 The tap density of the positive electrode black powder is within the above range, which is beneficial to improving the subsequent recovery rate of Fe and Li elements.
[0039] The embodiment of the present application also provides a method for recovering positive electrode black powder, comprising the following steps:
[0040] S1. Discharging the retired lithium-ion battery and disassembling it to obtain the positive electrode sheet;
[0041] S2. Place the positive electrode sheet into a laser cleaning machine, and clean each surface of the positive electrode sheet for 0.75h to 4h at a laser wavelength of 405nm to 976nm and a cleaning power of 100W to 1000W, and then sieve to obtain positive electrode black powder;
[0042] The positive electrode black powder comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I (200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200) It is the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder.
[0043] The positive electrode black powder recovery method provided in the present application adopts laser cleaning, which removes the positive electrode black powder from the surface of the current collector aluminum foil through vaporization, shock waves, thermal elasticity, etc. The positive electrode black powder recovery rate is high and has good dispersibility, which significantly improves the subsequent wet leaching efficiency. In addition, the laser cleaning process does not require a cleaning medium, which greatly alleviates the degree of damage to the aluminum foil and effectively reduces the aluminum impurity content in the positive electrode black powder.
[0044] In some embodiments, the laser wavelength is 520nm to 976nm. For example, the laser wavelength can be 520nm, 635nm, 755nm, 808nm, 915nm, 940nm, 976nm, or a value in a range formed by any two of the above points. When the laser wavelength is within the above range, the quality of the recovered positive electrode black powder can be further improved, thereby improving the efficiency of wet recovery of leached lithium.
[0045] In some embodiments, the cleaning power is 100 W to 600 W. For example, the cleaning power can be 100 W, 200 W, 300 W, 400 W, 500 W, 600 W, or a value in a range formed by any two of the above points. When the laser cleaning power is within the above range, the quality of the recovered positive electrode black powder can be further improved, thereby improving the efficiency of wet recovery of leached lithium.
[0046] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.
[0047] Example 1
[0048] Embodiment 1 provides a method for recovering positive electrode black powder, comprising the following steps:
[0049] (1) After the retired lithium iron phosphate battery is completely discharged using a discharge device, it is automatically disassembled to obtain the positive electrode sheet, the negative electrode sheet and the separator respectively;
[0050] (2) placing the positive electrode sheet into a laser cleaning machine, and cleaning each side for 0.75 h at a laser wavelength of 976 nm and a cleaning power of 100 W to obtain a mixture of black powder and aluminum foil;
[0051] (3) The mixture obtained in step 2 was added into a vibrating screening machine with a sieve hole size of 0.1 mm and a screening time of 0.5 h to obtain positive electrode black powder.
[0052] The difference between Examples 2 to 8 and Example 1 is that the laser cleaning power is different, as shown in Table 1 for details.
[0053] The difference between Examples 9 to 16 and Example 1 is that the laser cleaning wavelengths are different, as shown in Table 1 for details.
[0054] The difference between Examples 17 to 24 and Example 1 is that the laser cleaning time is different, as shown in Table 1 for details.
[0055] The difference between Comparative Example 1 and Example 1 is that the laser cleaning power is 1500W.
[0056] The difference between Comparative Example 2 and Example 1 is that the laser cleaning wavelength is 248 nm.
[0057] The difference between Comparative Example 3 and Example 1 is that the laser cleaning time is 10 hours.
[0058] The physical properties of the positive electrode black powder in Examples 1 to 24 and Comparative Examples 1 to 3 are shown in Table 1. The XRD spectrum of the positive electrode black powder obtained in Example 1 is as follows: Figure 1 As shown in the figure, the particle size distribution diagram is as follows Figure 2 As shown, the test spectra of other embodiments are similar and are not listed one by one. The results are shown in Table 1 for details.
[0059] Table 1
[0060]
[0061]
[0062] Table 1 (continued)
[0063]
[0064]
[0065] The black powder obtained in the embodiment and the comparative example is subjected to wet recovery, and the process of wet recovery of lithium is as follows:
[0066] The positive electrode black powder is dissolved by 32% liquid alkali and filtered to separate the impurity Al into NaAlO 2 The solution and the filter residue containing lithium phosphate are obtained; the filter residue is then leached with 98% sulfuric acid and filtered to obtain a filtrate containing lithium iron phosphorus, and finally the filtrate containing lithium iron phosphorus is adjusted to pH value and then leached with sodium carbonate to obtain a lithium-containing precipitate. The efficiency results of the wet method for recovering lithium are shown in Table 2.
[0067] Table 2
[0068]
[0069]
[0070] By comparing Examples 1 to 24 with Comparative Examples 1 to 3, it can be seen that the efficiency of wet recovery of leached lithium is improved by controlling the ratio of the peak intensity of the 311 characteristic diffraction peak to the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder within a certain range.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A positive electrode black powder, characterized in that: The positive electrode black powder comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I (200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200) It is the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder.
2. The positive electrode black powder according to claim 1, characterized in that: The positive electrode black powder satisfies: 0.22°≤F (311) ≤0.31°, where F (311) It is the half-peak width of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder.
3. The positive electrode black powder according to claim 1, characterized in that: The positive electrode black powder satisfies: 0.15°≤F (200) ≤0.4°, where F (200) It is the half-peak width of the 200 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder.
4. The positive electrode black powder according to claim 1, characterized in that: The height H2 of the characteristic peak with the largest particle size and the height H1 of the characteristic peak with the highest volume percentage in the particle size distribution diagram of the positive electrode black powder satisfy the following conditions: 0.12≤H2 / (H1+H2)≤0.
23.
5. The positive electrode black powder according to claim 1, characterized in that: The positive electrode black powder contains impurity elements, the impurity elements contain Al element, the content of the Al element is A, and satisfies: A≤2.5wt%.
6. The positive electrode black powder according to claim 1, characterized in that: The positive electrode black powder contains impurity elements, the impurity elements include at least one of Al, Cu, Mg, B, Ca, W, Cr, Zr, Ti, La, and V, the total content of the impurity elements is C, and satisfies: C≤3wt%.
7. The positive electrode black powder according to claim 1, characterized in that: The specific surface area B of the positive electrode black powder satisfies: 3.3m 2 / g≤B≤7m 2 / g.
8. The positive electrode black powder according to claim 1, characterized in that: The powder conductivity K of the positive electrode black powder 20KN satisfies: 0.05S / cm≤K≤0.35S / cm.
9. The positive electrode black powder according to claim 1, characterized in that: The tap density TD of the positive electrode black powder satisfies: TD≤1.12g / cm 3 .
10. A method for recovering positive electrode black powder, characterized in that: The steps include: S1. Discharging the retired lithium-ion battery and disassembling it to obtain the positive electrode sheet; S2. Place the positive electrode sheet into a laser cleaning machine, and clean each surface of the positive electrode sheet for 0.75h to 4h at a laser wavelength of 405nm to 976nm and a cleaning power of 100W to 1000W, and then sieve to obtain positive electrode black powder; The positive electrode black powder comprises a lithium-containing phosphate having an olivine structure, and the positive electrode black powder satisfies: I (311) / I (200) ≥2, where I (311) is the peak intensity of the 311 characteristic diffraction peak in the X-ray diffraction pattern of the positive electrode black powder, I (200) It is the peak intensity of the 200 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode black powder.
Citation Information
Patent Citations
Method of disposing of lithium battery
CN1973399A
Method for recovering electrode of power storage device, method for manufacturing power storage device, and electric storage device
JP2024144832A
Method for compensating lithium composition of recovered cathode materials of used lithium ion battery
KR102568593B1
Lithium Battery Treatment Method
US20080050295A1
Process for the recovery of lithium from waste lithium ion batteries
US20220274841A1